The Reading Cycle: Strategy for Boosting Non-reading Children - Villegas Herrera, María Soledad (Pensando Psicología, 2015)
Purpose: The process of learning to read and write starts in early childhood through the use of genuine reading and writing conducts in the family context and at educational centers. The purpose of this experience was to improve the quality of reading of non-reading children in basic primary education. Topic: The program entitled “Aprendizaje Inicial de la Lectura, Escritura y Matemática” (Initial Learning of Reading, Writing and Mathematics) of the Pontificia Universidad Católica de Chile (AILEM UC) consists of a set of strategies to boost learning using a series of reading and writing strategies. It has been implemented at different schools in the country beginning in 2002. Development: A successful experience is presented that was carried out in Chile, in the city of La Serena, using the “Reading Cycle” (“Ciclo de lectura”), one of the strategies of the ailem program, with a group of first graders who were behind in learning to read. Conclusions: With the work systematically carried out over a two month period by the consultants, applying the strategy, a group of non-reading children or those who were behind in their reading skills, at the end of the year was able to read, at least syllabilcally.